The requirements from the international conventions for protecting an employee with a disability in the individual labour dispute - Nguyen, Binh An (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
A review of the literature has been also done examining the effects of the UN and ILO conventions regarding the employment of disabled people. The "labour dispute" legislation is very structured in the domain of Vietnam as they are systematically trying to match the international standard due to recent multiple free trade agreements. All the disabled employees can employ the mechanism of negotiation and conciliation to solve their disagreement or it can be solved by the courts as well. Both individual or collective labour disputes can be efficiently manoeuvred by the potent legislation of Vietnam and it has systematically assisted the disabled employees.